Behavioural consistency across metamorphosis in a neotropical poison frog - Bégué, Lauriane (Evolutionary ecology, 2023)
Animals often show consistency in their behavioural repertoire across time and/or contexts that differs from other individuals of the same population, i.e. animal personality. We currently have quite an incomplete understanding of the factors that lead to behavioural traits remaining stable - or becoming decoupled - over an animal's lifetime. In this study, we investigated the role of metamorphosis in the development of animal personality in a Neotropical poison frog, a species that undergoes drastic morphological and ecological changes during its development. We used lab-reared individuals of the brilliant-thighed poison frog Allobates femoralis to assess if consistent individual differences are already present at the tadpole stage, and if these differences are maintained throughout metamorphosis. We found evidence for two personality traits, exploration and boldness, already present in A. femoralis tadpoles. Despite the drastic changes in morphology, physiology, and habitat in the transition from tadpoles to metamorphs, personality traits persisted throughout metamorphosis, suggesting a physiological and/or genetic basis for the measured behavioural traits. We also found that exploration and boldness related behaviours were correlated with growth speed. Very bold and explorative individuals took fewer days until metamorphosis compared to very shy and non-explorative ones, which is in line with the concept of a Pace-of-Life Syndrome. These findings provide important insights into the proximate mechanisms that generate personality in species with complex life cycles